(untitled) (Lundiana: International Journal of Biodiversity, 2002)
The Thelypteridaceae Pic. Serm. is represented in the state of São Paulo by 56 species, one in the genus Macrothelypteris (H. Itô) Ching [M. torresiana (Gaudich.) Ching], and 55 in the genus Thelypteris Schmidel, the later distributed among five subgenera. The results on a revision of the species of Thelypteridaceae occurring in São Paulo state concerning Thelypteris subg. Cyclosorus (Link) C. V. Morton and Thelypteris subg. Steiropteris (C. Chr.) K. Iwats. are presented here. Thelypteris subg. Cyclosorus is represented by seven species: T. berroi (C. Chr.) C. F. Reed, T. conspersa (Schrad.) A. R. Sm., T. dentata (Forssk.) E. St. John, T. grandis A. R. Sm., T. hispidula (Decne.) C. F. Reed, T. interrupta (Willd.) K. Iwats. and T. patens (Sw.) Small. Thelypteris subg. Steiropteris is represented by four species: T. decussata (L.) Proctor, T. gardneriana (Baker) C. F. Reed, T. hatschbachii A. R. Sm. and T. leprieurii (Hook.) R. M. Tryon. Keys to the genera of Thelypteridaceae, subgenera of Thelypteris and species of Thelypteris subg. Cyclosorus and Thelypteris subg. Steiropteris, descriptions, illustrations, commentaries and data on geographical distribution are provided.